2016
DOI: 10.1007/s10157-016-1261-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum chloride level with mortality and cardiovascular events in chronic kidney disease: the CKD-ROUTE study

Abstract: Low Cl was associated with increased mortality and risk of CV events in pre-dialysis CKD patients. Cl may be an additional prognostic indicator in CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 29 publications
4
41
0
Order By: Relevance
“…These include changes of urine dilution and concentration in response to antidiuretic hormone, and alteration of water and Na and CI reabsorption and excretion 13,14 . Previous studies have reported that dysnatremias and hypochloremia are associated factors for mortality in patients with chronic kidney disease (CKD), with or without dialysis [15][16][17][18][19][20][21][22] . Thus, dyschloremias and dysnatremias have been proposed as potential useful factors for mortality prediction in this population [15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…These include changes of urine dilution and concentration in response to antidiuretic hormone, and alteration of water and Na and CI reabsorption and excretion 13,14 . Previous studies have reported that dysnatremias and hypochloremia are associated factors for mortality in patients with chronic kidney disease (CKD), with or without dialysis [15][16][17][18][19][20][21][22] . Thus, dyschloremias and dysnatremias have been proposed as potential useful factors for mortality prediction in this population [15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Although somewhat limited by the small sample size, the results of the present study suggest that ND2-237 Leu/Met polymorphism and coffee consumption exert a joint association with serum chloride levels in middle-age male Japanese health checkup examinees; namely, serum chloride levels were positively associated with the amount of daily coffee consumption in men with the ND2-237Leu genotype. Moreover, the risk of low levels of serum chloride, which has been shown to be associated with a higher risk of CVD and mortality [ 8 , 9 , 10 , 11 , 12 ], was significantly lower in men with the ND2-237Leu genotype who consumed ≥4 compared with <1 cup of coffee per day. However, coffee consumption did not appear to affect serum chloride levels in men with the ND2-237Met genotype.…”
Section: Discussionmentioning
confidence: 99%
“…A potential contradiction may exist in relation to these findings. Although low serum chloride levels have been shown to be associated with an increased risk of both all-cause and CVD mortality [ 8 , 9 , 10 , 11 , 12 ], the results of our previous study showed that serum chloride levels were significantly lower in men who had the ND2-237Met genotype—who have been reported to have a genetic tendency toward longevity [ 13 ] and resistance against life-threatening diseases [ 14 , 15 , 16 , 17 , 18 ]—compared with those with the ND2-237Leu genotype [ 24 ]. Therefore, the genetic advantage of having the ND2-237Met genotype may surpass the physiological disadvantage of having low serum chloride levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalences of hyperuricemia and electrolyte abnormalities in patients with CKD have been reported in clinical and epidemiological studies [8][9][10][11][13][14][15][16][17][18]. Recently, analyses of realworld conditions of patients with CKD were performed based on electronic health records [12,[19][20][21][22]; these studies included analyses of electrolyte abnormality prevalences among patients with CKD [12].…”
Section: Introductionmentioning
confidence: 99%